2014
DOI: 10.1186/2193-1801-3-645
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic silver nanoparticles associated with silver chloride nanoparticles (Ag@AgCl) produced by laccase from Trametes versicolor

Abstract: In the present study, semi-purified laccase from Trametes versicolor was applied for the synthesis of silver nanoparticles, and the properties of the produced nanoparticles were characterized. All of the analyses of the spectra indicated silver nanoparticle formation. A complete characterization of the silver nanoparticles showed that a complex of silver nanoparticles and silver ions was produced, with the majority of the particles having a Ag2+ chemical structure. A hypothetical mechanistic scheme was propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…3) was compatible with that described by Durán et al, 31 who reported diffraction patterns for silver nanoparticles with Bragg peaks for (331) in (2Ɵ = 85º), which were ascribed to silver chloride nanoparticles. We also observed a basal level of Ag/AgCl-NPs formation in fresh medium (i.e., with no interference of yeast biological activity) and in culture medium containing heat-killed yeasts (Fig.…”
Section: Page 28 Of 52 Rsc Advancessupporting
confidence: 91%
“…3) was compatible with that described by Durán et al, 31 who reported diffraction patterns for silver nanoparticles with Bragg peaks for (331) in (2Ɵ = 85º), which were ascribed to silver chloride nanoparticles. We also observed a basal level of Ag/AgCl-NPs formation in fresh medium (i.e., with no interference of yeast biological activity) and in culture medium containing heat-killed yeasts (Fig.…”
Section: Page 28 Of 52 Rsc Advancessupporting
confidence: 91%
“…Das et al (2009) and Kumar et al (2012) reported the lysozymemediated synthesis of Ag o nanoparticles in aqueous solution under controlled pH and light conditions. XRD pattern showed that the reaction of laccase, obtained from Trametes versicolor, with silver ions was compatible with the cubic phase of Ag°nanoparticles with diffractions points at planes of the facet centered cubic (FCC) structure (JCPDS file: 65-2871 or ICSD Code 64994) that coexisted with the cubic phase of AgCl planes (JCPDS file: 31-1238 or ICSD Code 64734) (Durán et al 2014b).…”
Section: Yeastsmentioning
confidence: 99%
“…T. versicolor, also known as Coriolus versicolor [49,50], has been investigated in several studies for the removal of PPCPs both in batch and continuous reactors [24,26,27,43,51,52,53]. Depending on the strain, T. versicolor may contain laccase, LiP and MnP, with laccase being the predominant enzyme in some strains.…”
Section: Degradation Capacity Of Different Wrfmentioning
confidence: 99%